Sourcewise represented Green’s function of the circular waveguide - Prijmenko, S.D.; Bondarenko, L.A. (Вопросы атомной науки и техники, 2007)
Singular part of the Green’s function of unbounded space is singled out in explicit form and contains all singularities, including a delta-shaped singularity. The problem of construction of Green’s function for a field is solved, as a problem for diffraction of potential and rotational components electric field intensity of a point current source on the circular waveguide walls. The singling out of the electric field intensity singularity in an explicit form about a source enables to develop an effective algorithm of Green’s function calculation at any distance between the source point and observation point in a circular waveguide.